Transfer learning with convolutional neural networks for diabetic retinopathy image classification - Kandel, Ibrahem (2020)
Kandel, I., & Castelli, M. (2020). Transfer learning with convolutional neural networks for diabetic retinopathy image classification. A review. Applied Sciences (Switzerland), 10(6), [2021]. https://doi.org/10.3390/app10062021 ---------------------------------------------------------------------- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia) under projects DSAIPA/DS/0022/2018 (GADgET), DSAIPA/DS/0113/2019 (AICE), and by the financial support from the Slovenian Research Agency (research core funding No. P5-0410). M.C. also acknowledges the support of NVIDIA Corporation